2011
DOI: 10.1517/13543784.2011.609167
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Mcl-1 for the therapy of cancer

Abstract: Introduction Human cancers are genetically and epigenetically heterogeneous and have the capacity to commandeer a variety of cellular processes to aid in their survival, growth and resistance to therapy. One strategy is to overexpress proteins that suppress apoptosis, such as the Bcl-2 family protein Mcl-1. The Mcl-1 protein plays a pivotal role in protecting cells from apoptosis and is overexpressed in a variety of human cancers. Areas covered Targeting Mcl-1 for extinction in these cancers, using genetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
160
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(167 citation statements)
references
References 97 publications
(105 reference statements)
7
160
0
Order By: Relevance
“…Of note, we found that the inhibition of Mcl-1 using siRNA also resulted in significant apoptosis in the absence of etoposide, which is in contrast to the finding of others on solid tumors (Thallinger et al, 2003, Thallinger et al, 2004. However, this observation is similar to that found on other studies on hematological malignancies (Hussain et al, 2007;Quinn et al, 2011), illustrating the important biological role of Mcl-1 in leukemic cells. In addition, siMcl-1, in combination with etoposide dramatically enhanced apoptosis compared with siRNA alone or etoposide alone.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Of note, we found that the inhibition of Mcl-1 using siRNA also resulted in significant apoptosis in the absence of etoposide, which is in contrast to the finding of others on solid tumors (Thallinger et al, 2003, Thallinger et al, 2004. However, this observation is similar to that found on other studies on hematological malignancies (Hussain et al, 2007;Quinn et al, 2011), illustrating the important biological role of Mcl-1 in leukemic cells. In addition, siMcl-1, in combination with etoposide dramatically enhanced apoptosis compared with siRNA alone or etoposide alone.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, some reports have indicated that Mcl-1 is needed for the function of hematopoetic cell systems and survival of tumor cells (Brunelle et al, 2009;Yecies et al, 2010;Glaser et al, 2012). Studies have shown that Mcl-1 is overexpressed in various malignancies and downregulation of this protein by antisense oligonucleotide (ASO) or RNA interference (RNAi) technology induced apoptosis and sensitized tumor cells to anti-cancer agents (Chetoui et al, 2008;Skoda et al, 2008;Warr and Shore, 2008;Quinn et al, 2011;Akagi et al, 2013). Moreover, elevated expression of Mcl-1 at the time of leukemic relapse, offers a possible explanation to the role of this protein in the survival of leukemia cells after chemotherapy (Kaufmann et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Showing off-target effects, these compounds were considered as putative BH3 mimetics (5,9,(13)(14)(15)(16). Given that MCL-1 has emerged as a critical prosurvival factor in a number of malignancies and in drug resistance (17), there is an urgent need to identify MCL-1-specific BH3 mimetics (18,19). The development of small molecules capable of targeting all the main antiapoptotic BCL-2 proteins is also of clear therapeutic interest (8,(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Mcl-1 has been implicated in the regulation of mitochondrial bioenergetics and morphogenesis 8 , chemotherapy-induced senescence 9 , starvation and Ras oncogene-induced autophagy 10,11 , suggesting that its contribution to tumorigenesis may go beyond evading apoptosis. Targeting Mcl-1 is emerging as a potential therapeutic strategy [12][13][14][15][16] and therefore a deeper understanding of the mechanisms controlling Mcl-1 levels and function is of paramount importance. In comparison with other anti-apoptotic members of the Bcl-2 family, Mcl-1 exhibits some unique features including its tight regulation by complex mechanisms at the multiple levels of expression, translation and stability 17 .…”
mentioning
confidence: 99%